Da fotografia à instalação: percursos pelo universo gemológico - Pereira, Camila Zappe (2018)
Permeating digital processes this project aimed to develop a poetic production that investigated the incorporation of gemological materials as thematic in the contemporary languages of art. Through a plural artistic approach that included photography, collage, sound manipulation and video, this research had the purpose of exploring the displacement of the gem from the physical object to the reference in digital art. The hybrid deployments of gemological materials in the field of art, science and technology proposed a possibility of approaching the public of art with this universe and promoted, in the face of poetic research, a reflection on the plastic possibilities and environmental issues that guide these resources. Through an audiovisual and critical research that went through the photographic act and the digital art, it was intended to contribute with new connections of knowledge and to attenuate to the poetic potentialities and questionings around the gemological universe.